Cracking mechanism and degradation performances of HTV silicone rubber with interfacial defects under acid and thermal stress. (September 2021) - Gou, Bin; Xie, Congzhen; Xu, Huasong; Du, Yan; Wang, Rui; Li, Licheng; Fan, Weinan
Highlights: The cracking phenomenon of HTV SIR sheath in composite insulators was realistically reappeared. The cracking process and mechanism of HTV SIR with interfacial defects were explored. Thermal stability, hydrophobicity and dielectric properties of HTV SIR with interfacial defects in different aging condition were studied. The facilitated effect of interface defects on the aging of HTV SIR was proved. Abstract: High temperature vulcanized (HTV) silicone rubber (SIR), as the sheath of composite insulators, is widely used as the insulation device in transmission lines due to their excellent hydrophobicity and pollution flashover resistance. However, the interfacial defects of insulators and severe operating environment will accelerate the aging of HTV SIR sheath, seriously affecting the operation reliability of electrical equipment. Herein, the samples designed with different sizes of interfacial defects are aged under water, sulfuric acid and nitric acid at 80 °C, respectively. The results show that a large number of cracks appear on the surface of HTV SIR samples with interfacial defects after nitric acid treatment at 80 °C for more than 2 days, while samples with no interfacial defects aged under same condition for 8 days maintain unchanged. According to the results of the micro morphology of the sample, the crack is caused by the interfacial stress of the sample. In addition, after nitric acid treatment, the thermal stability, tensile and dielectric properties of HTV SIR with interfacial defects decreased significantly. The initial decomposition temperature decreases by about 30 °C, while the residual weight increases by about 2.5%. Meanwhile, the tensile strength and fracture strain decrease from 4.58 MPa and 470% to 2.07 MPa and 130% respectively, proving that cracks caused by interfacial defects can critically avianize the mechanical properties and thermal stability of HTV SIR. Also, there is an extra dielectric loss peak appearing in the frequency range of 10 2 –10 4 Hz, which attributed to water invading and the MWS polarization at cracks. By aging HTV SIR with artificial interfacial defects under thermal and acid stress, the HTV SIR cracking phenomenon of composite insulators under severe operating environment is successfully simulated. This work can provide theoretical support ulteriorly for studying the cracking mechanism and the corresponding aging characteristics of HTV SIR used in composite insulators.